Simulation model of the technological complex of charge preparation for sinter production - Зобнин, Борис Борисович; Горбенко, Олег Александрович; Ажипа, Игорь Анатольевич; Яковлев, Роман Андреевич (Eastern-European Journal of Enterprise Technologies, 2015)
A simulation model of the technological complex of charge preparation for sinter production was developed.This approach stems from the fact that the dimension of tasks and non-formalizability of objects do not allow to use rigorous mathematical methods.Integrated debugging and testing of the system on the real object is impossible without the simulation model considering the insecurity of the artificial creation of emergency situations.Using the developed simulation model, the factors, affecting the charge quality stabilization were investigated.It was proposed to build a domain model using ontology that allows to avoid contradictions in determining the type of the class hierarchy. Also, it was proposed to use the original identification procedure of weighted average values of the content of chemical elements and oxides in the homogenization tank, as well as the multiagent approach for simulating emergency situations. As a result of the research, it was found that the characteristics of the formed stack from various types of disruptions in the homogenization unit.Estimates of trends in the monitored parameters at the homogenization unit synchronization failures were obtained, and contributions of the change of technological processes to the occurrence and magnitude of the anomalous zones in the stack were defined.Using the resulting model allows to solve the stack formation management problem.